2003
DOI: 10.1023/a:1023998308892
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was designed to determine factors that influence female and male condom use among Central American women, applying the theory of planned behavior. A cross-sectional design was employed and a sample of 175 Central American women, 18-50 years old, was recruited from a community-based clinic in Los Angeles County. Participants in this study were interviewed face-to-face. Attitude, subjective norm, and perceived behavioral control explained 41% and 45% of the variation in the intention to use male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our results, however, are at odds with previous research suggesting that recent immigrants and less acculturated Latino females reported fewer sexual partners (Kasirye et al, 2005; Sabogal, Perez-Stable, Otero-Sabogal, & Hiatt, 1995). Complementary studies also found that greater number of sexual partners with more consistent condom use was reported among more acculturated Latinas (Salabarría-Peña, Lee, Montgomery, Hopp, & Muralles, 2003; Caetano & Hines, 1995). Our study did not account for the ethnic background of sexual partners, which may be helpful in assessing levels of acculturation and risk patterns of this group.…”
Section: Discussionmentioning
confidence: 89%
“…Our results, however, are at odds with previous research suggesting that recent immigrants and less acculturated Latino females reported fewer sexual partners (Kasirye et al, 2005; Sabogal, Perez-Stable, Otero-Sabogal, & Hiatt, 1995). Complementary studies also found that greater number of sexual partners with more consistent condom use was reported among more acculturated Latinas (Salabarría-Peña, Lee, Montgomery, Hopp, & Muralles, 2003; Caetano & Hines, 1995). Our study did not account for the ethnic background of sexual partners, which may be helpful in assessing levels of acculturation and risk patterns of this group.…”
Section: Discussionmentioning
confidence: 89%
“…Hispanic women are less likely than their non-Hispanic White and Black counterparts to work outside the home. Some research with younger Hispanics suggests that when women are unemployed, more traditional (with regard to acculturation), less educated, and poorer, they have a more difficult time negotiating safer sex or condom use with their partners (Bowleg, Belgrave, & Reisen, 2000; Dixon, Antoni, Peters, & Saul, 2001; Salabarria-Pena, Lee, Montgomery, Hopp, & Muralles, 2003; Saul et al, 2000). Hispanic women have poorer health status, use fewer health services, and suffer from higher rates of disease, disabilities, and early death.…”
Section: Socioeconomic Factors and Hivmentioning
confidence: 99%
“…Of course, to overcome the low correlation between attitude and behavior, existing theories likewise argue that individuals possess subjective norms that reflect the attitudes of their significant others [30]. Such a model clearly predicts the CUB of general population groups, including immigrants [31], [32]. However, this model is relatively deficient in consideration of the specific contexts of sexual relations such as sexuality and the degree of the pursuit of sexual risk behavior.…”
Section: Discussionmentioning
confidence: 99%